Computation of Magnetic Field of Coil using a Finite Element Method - Tarvydas, P. (Elektronika ir Elektrotechnika, 2001)
Electromagnetic devices are widely applied in various spheres of engineering. Electromagnetic devices have their behavior governed by the electromagnetic fields which flow in them. Magnetic fields can be calculated or found experimentally. Theoretically calculating the field of the device it is necessary to describe its geometry and having completed the computer calculation of fields the future characteristics of these devices can be modelled. The characteristic features of the modelling of magnetic fields of coil by means of the finite element method were examined. Algorithm for the modelling are presented. The calculation of the magnetic field of cylindrical coil was carried out. Finite element mesh and distribution of magnetic field strength in 2-D space are presented.